Transformational Leadership And Employee Engagement: A Study On Organizational Success In The Digital Age - Agus Suyatno; Indra Krishernawan; Klemens Mere (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Transformational leadership is characterized by leaders who inspire, motivate, and intellectually stimulate their followers, fostering an environment where employees feel valued and empowered to achieve beyond expectations (Bass, 1985). Such leaders focus on four key components: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This study adopts a systematic literature review (SLR) approach to explore the relationship between transformational leadership and employee engagement, and how these factors contribute to organizational success in the digital age. The systematic review clearly demonstrates that transformational leadership significantly enhances employee engagement, which serves as a powerful driver of organizational success in the digital era. Organizations that prioritize the development of transformational leadership competencies are better equipped to navigate digital disruptions, foster innovation, and retain top talent.